2010
DOI: 10.2466/pms.110.2.453-462
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Use of Number Representation is Independent of Test Instruction in Random Number Generation

Abstract: The effects of different instructions on verbal random number generation were examined in 40 healthy students who attempted to generate random sequences of the digits 1 to 6. Two groups of 20 received different instructions with alternative numerical representations. The Symbolic group (Arabic digits) was instructed to randomize while continuously using the analogy of selecting and replacing numbered balls from a hat, whereas the Nonsymbolic group (arrays of dots) was instructed to imagine repeatedly throwing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Our results suggests a gravitational bias on the spatial distribution of numbers. The random number generation task has been previously adopted to investigate the properties of the non-verbal mental number line (Loetscher & Brugger 2007;Strenge & Rogge, 2010). Loetscher, Schwarz, Schubiger and Brugger (2008) found that actively turning the head to the left or right biased participants' responses towards smaller or larger numbers respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggests a gravitational bias on the spatial distribution of numbers. The random number generation task has been previously adopted to investigate the properties of the non-verbal mental number line (Loetscher & Brugger 2007;Strenge & Rogge, 2010). Loetscher, Schwarz, Schubiger and Brugger (2008) found that actively turning the head to the left or right biased participants' responses towards smaller or larger numbers respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Small numbers are associated with the left side of space, while larger numbers are associated with the right side (Dehaene, 1992). Results indicated a spatial-numerical interaction in random number generation: numbers were spontaneously remapped to spatial locations along a number line (Loetscher & Brugger 2007;Strenge & Rogge, 2010). Additionally, participants seem to mentally visualize the order of digits to facilitate the process of number generation (Towse 1998;Towse & Neil, 1998).…”
Section: Introductionmentioning
confidence: 99%